Practical implementation of repetition codes - Torres, Paulo (2018)
This work consists in the development of software with the main objective of increasing the quality of the communication system with Repetition Codes and GFSK modulation. To evaluate the probability of error we used simulation in software Python and implemented with hardware (Raspberry Pi, Arduino and transceiver NRF24L01).